2019
DOI: 10.1002/kjm2.12084
|View full text |Cite
|
Sign up to set email alerts
|

The research of transgenic human nucleus pulposus cell transplantation in the treatment of lumbar disc degeneration

Abstract: The present study determines whether the in vivo injection of TGFβ1 and CTGF mediated by AAV2 to transfect nucleus pulposus cells in degenerative lumbar discs can reverse the biological effects of rhesus lumbar disc degeneration. A total of 42 lumbar discs obtained from six rhesus monkeys were classified into three groups: experimental group, control group, and blank group. Degenerative lumbar discs were respectively injected with double gene-transfected human nucleus pulposus cells using minimally invasive te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This review aims to focus on the choice of cell source for regenerative approaches and thus will not discuss the combinations with biomaterial and growth factors which have been reviewed elsewhere. 44,[91][92][93][94][95][96][97][98][99][100] NP tissue also contains a population of NP progenitor cells 98,[101][102][103] which have been suggested to be NPderived stem cells although their full characterization as stem cells has not been completed. NP progenitors in vitro are presented as elongated spindle shape cells, 104 which are positive for Tie2 and express stem cell genes (eg, Sox2, Oct3/4, Nanog, CD133, Nestin, and neural cell adhesion molecule).…”
Section: Proposed Cell Sources For Nucleus Pulposus Regenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…This review aims to focus on the choice of cell source for regenerative approaches and thus will not discuss the combinations with biomaterial and growth factors which have been reviewed elsewhere. 44,[91][92][93][94][95][96][97][98][99][100] NP tissue also contains a population of NP progenitor cells 98,[101][102][103] which have been suggested to be NPderived stem cells although their full characterization as stem cells has not been completed. NP progenitors in vitro are presented as elongated spindle shape cells, 104 which are positive for Tie2 and express stem cell genes (eg, Sox2, Oct3/4, Nanog, CD133, Nestin, and neural cell adhesion molecule).…”
Section: Proposed Cell Sources For Nucleus Pulposus Regenerationmentioning
confidence: 99%
“…However, the culture of isolated cells prevents all cell-matrix interactions and signaling and thus, NP cells could act differently when cultured in in vivo systems. 133 NP cells transplantation into in vivo models have also been investigated and studies have shown that the transplanted NP cell remain viable for a number of weeks and months; allogeneic expanded rtNP cells remained viable for 4 weeks in a rat model 134 ; in a canine model, cryopreserved autologous cNP cells were observed at 12 weeks 115 and 12 months of allogeneic expanded cNP cells 62 ; xenogeneic transplantation of a hNP established cell line were sustained in a rabbit model for 8 and 24 weeks, 98,135 12 weeks in a monkey model 100 and 12 weeks in a canine model. 116 Interestingly, transplanted NP cells were mainly localized in the injected zone, with observation of cells migrating into the inner AF in canine and rat treated models.…”
Section: Cell Survival In the Intervertebral Disc Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The tissue section and immunohistochemical procedure were performed according to Wang et al [ 19 ]. The primary antibody of OVR (1:1000, RD Systems, Catalog: AF2258, Minneapolis, MN, USA), and the secondary antibody (1:1000, Servicebio, Catalog: GB23204, Wuhan, China) were used to identify the expression and localization of OVR in each follicle level through the specific light to dark brown staining.…”
Section: Methodsmentioning
confidence: 99%